(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate macular thickness and retinal nerve fiber layer thickness in pediatric patients with primary malnutrition. Material and Methods: Macular and peripapillary retinal nerve fiber layer thicknesses of 90 pediatric patients with primary malnutrition were measured by spectral field optical coherence tomography. These findings were compared with the data of 50 age-matched healthy children.Results: There were no statistically significant differences in terms of age, gender and refractive status between the groups. In the primary malnutrition group, 17 of 90 patients had decreased retinal nerve fiber layer values. There were no patients with decreased retinal nerve fiber layer values in the control group and this difference was statistically significant (p 0.001). Retinal nerve fiber layer was thinner in the patients with primary malnutrition with low serum vitamin D and ferritin levels. (p=0.025, p0.001, respectively) We found that as the severity of malnutrition increased according to weight and height, the thinning of the peripapillary retinal nerve fiber layer increased, especially in the temporal segment. (r: -0.249 p=:0.003, r: -0.251 p=0.002, respectively). Conclusion: Undernutrition with micronutrient deficiencies may cause retinal nerve fiber layer thinning in pediatric cases. Therefore, it should be treated early before vision defects occur.